Novel exploration of Raman microscopy and non-linear optical imaging in adenomyosis - Shen, Zhuowei; He, Yingying; Shen, Zhuoyi; Wang, Xuefei; Wang, Yang; Hua, Zhengyu; Jiang, Nan; Song, Zejiang; Li, Rui; Xiao, Zhen (Frontiers in Medicine, 2022)
Background: Adenomyosis is a common gynecological disease in women. The survey found that about 82% of patients with adenomyosis chose hysterectomy. However, women of childbearing age are more likely to undergo surgery to preserve the uterus. Because it is difficult to determine the extent of adenomyosis, it is almost impossible to resect adenomyosis that retains the uterus. Methods: With the informed consent of the ethics committee and the patient, we cut 3 fresh frozen sections of each tissue sample for HE staining, Raman spectroscopic analysis and photography under CARS and SHG microscope, and conducted comparative observation and analysis. Results: We found that there were two characteristic peaks 1155cm-1 and 1519cm-1 in Raman spectrum, which were significantly different from the normal parts. The substances shown in cars spectrum were the substances represented by the 1519cm-1 peaks. SHG showed the distribution of collagen in the focus of adenomyosis. Conclusions: Through this study, we found the feasibility of diffraction spectrum in the diagnosis of adenomyosis and the judgment of the focus boundary of adenomyosis.